Respiratory virus infections after allogeneic stem cell transplantation: Current understanding, knowledge gaps, and recent advances - Piñana, Jose L.; Pérez, Ariadna; Chorão, Pedro; Guerreiro, Manuel; García‐Cadenas, Irene; Solano, Carlos; Martino, Rodrigo; Navarro, David (Transplant infectious disease, 2023)
Before the COVID‐19 pandemic, common community‐acquired seasonal respiratory viruses (CARVs) were a significant threat to the health and well‐being of allogeneic hematopoietic cell transplant (allo‐HCT) recipients, often resulting in severe illness and even death. The pandemic has further highlighted the significant risk that immunosuppressed patients, including allo‐HCT recipients, face when infected with SARS‐CoV‐2. As preventive transmission measures are relaxed and CARVs circulate again among the community, including in allo‐HSCT recipients, it is crucial to understand the current state of knowledge, gaps, and recent advances regarding CARV infection in allo‐HCT recipients. Urgent research is needed to identify seasonal respiratory viruses as potential drivers for future pandemics.